2006
DOI: 10.3168/jds.s0022-0302(06)72273-1
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Survival from Gossypol-Fed Heifers after Transfer to Lactating Cows Treated with Human Chorionic Gonadotropin

Abstract: Objectives were to determine the effects of gossypol exposure during early embryo development on embryonic survival after transfer of frozen and thawed embryos to lactating dairy cows treated with human chorionic gonadotropin (hCG). Holstein cows (n = 269) were either treated or not treated with 3,300 IU of hCG on d 5 of the estrous cycle and received an embryo collected from heifers fed or not fed gossypol. Embryo donor heifers consumed either 0 or 12 g/d of free gossypol for 76 d prior to embryo collection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
2
6
1
3
Order By: Relevance
“…Concentrations of progesterone were elevated by hCG and pregnancy status compared with saline controls and lack of pregnancy in the present study, respectively, corroborating similar reports in lactating dairy cows Galvão et al, 2006;Stevenson et al, 2007) and in dairy heifers (Schmitt et al, 1996a). Although we did not detect increased progesterone in cows in which hCG failed to produce new luteal structures, previous studies reported that progesterone secretion by original CL was enhanced (Stevenson et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concentrations of progesterone were elevated by hCG and pregnancy status compared with saline controls and lack of pregnancy in the present study, respectively, corroborating similar reports in lactating dairy cows Galvão et al, 2006;Stevenson et al, 2007) and in dairy heifers (Schmitt et al, 1996a). Although we did not detect increased progesterone in cows in which hCG failed to produce new luteal structures, previous studies reported that progesterone secretion by original CL was enhanced (Stevenson et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Frequency of hCG-induced luteal structures in the present study was consistent with the findings of the latter 2 studies. Incidence of ≥2 new luteal structures in our study (17.2%) was independent of the number of pretreatment CL and pregnancy status but was slightly less than that reported in other lactating dairy cows (24.8%; Galvão et al, 2006). Although the level of milk production was not associated with ovulatory response to hCG , cows enrolled in the present study averaged more than 46 kg of ECM per day, and those producing greater than 46 kg of ECM were less likely to form new luteal structures after to hCG.…”
Section: Discussioncontrasting
confidence: 82%
“…Chagas e Silva and Lopes da Costa (2005) reported no effect of hCG treatment on d 7 on P/ET in dairy heifers; however, pregnancy loss was not reported in that study. In addition, treatment with hCG 5 d after ovulation did not affect P/ET for lactating Holstein cows receiving ET 7 d after induction of ovulation (Galvão et al, 2006). In mature beef cows, treatment with hCG at ET 7 d after ovulation increased P/ET, but no difference was noted in pregnancy loss (Wallace et al, 2011).…”
Section: Effect Of Treatment On Pregnancy Outcomes and Pregnancy Lossmentioning
confidence: 81%
“…The embryo diameter was significantly and dose dependently reduced. These effects of gossypol were also observed in dairy cows receiving embryos from heifers fed gossypol (Galvao et al, 2006), which suggests that negative effects in early embryo development persist during maintenance of pregnancy.…”
Section: Ruminantsmentioning
confidence: 80%